The Flipside of New Public Management: An Inquiry into the Challenges Facing Outsourced Workers in South Africa - Mthembu, Zamazulu; Ashade, Oladimeji; Mutereko, Sybert (African Journal of Inter/Multidisciplinary Studies, 2021)
Inspired by the new public management (NPM) philosophy, public sector institutions have engaged private companies by outsourcing non-core services for improved service delivery, lowering government expenditure, and creating opportunities for employment. There is evidence suggesting that the public sector has witnessed industrial conflicts occasioned by labour unrest among outsourced workers. This paper explores how the employees of contract companies perceive outsourcing and how outsourcing has affected them. Using a non-probabilistic sampling technique, the study mixes both qualitative and quantitative techniques to show that the outsourced workers do not see outsourcing in good light. The viewpoint of participants revealed that the outsourced workers were not pleased with the condition of work under different management. These findings have significant implications for broadening the understanding of the plight of the outsourced workers in the public sector. This study has raised important questions about the nature of outsourcing in the public sector and aroused the consciousness that the challenge facing outsourced workforce persists despite the premium placed on NPM in literature. The study, therefore, recommends that the condition of service of outsourced workers in South Africa’s public departments be given due attention to forestall undesirable outcomes.